PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF PREPARING EDUCATORS FOR SCHOOL EDUCATION - N.M.Khujanazarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the pedagogical and psychological characteristics of preparing educators for school education.